Draft precis of evidence to be given before the Departmental Committee on Midwives
1928-09 1928 1920s 6 pages 2. resulted in the mother visiting one or the other to arrange for the confinement at an earlier date than had been usual and midwives have expressed the opinion that the chance thus given of advising the mothers made a definite difference in helping to save their lives later, though poverty and anxiety were so heavily thrown in the scales against them. The practice of giving ante-natal advice at the clinics is growing and it is to be noted that a woman will more readily undergo examination if the doctor is a woman. This is to be borne in mind when considering the facilities for training of medical students and is referred to later. 7. We attached special importance to the ante-natal supervision of the doctor who will be responsible for the confinement as well as to the attendance of the midwife. We would point out the following advantages:- (a) The doctor with a previous knowledge of the patient would be able to judge the kind of confinement, the probability of emergencies arising, and can advise the patient as to going into a Hospital or Maternity Home. (b) There is no danger of losing a life because of delay in getting a doctor or an emergency arising. (c) If necessary he can secure ante-natal examination by a consultant at the clinic. (d) As the midwife would be present throughout the period of labour, and in a normal case might conduct it herself, the whole time of the doctor would not be taken up - but a short visit might be sufficient. He would, however, be ready to come whenever required by the midwife and the reputation of both would be involved in preventing any possible failure through negligence. (e) The doctor would be available for the administration of chloroform whenever it should be in the interests of the patient to give it - not only for a forced delivery but for the prevention of pain and exhaustion. (f) In our country, those who can afford it have both a maternity nurse and a doctor. We think that all mothers should have an equal opportunity of a safe and healthy delivery. (g) The midwife should after the delivery visit as she does now, reporting to the doctor who would visit in normal cases less often but be prepared for fuller attendance whenever needed. 8. We recognise that we are proposing a very big step forward. It means the presence of a doctor at some 50 to 70% more cases. This means a great increase in the number of doctors taking midwifery cases and their training must be adequate to the task. 292/824/1/116